A new proposal for the design of confined masonry buildings - Marques, Rui Filipe Pedreira (2010)
Confined masonry has been efficiently used for buildings in Latin-America, Northern-Africa and Asia, even in seismic areas. However, despite all the research on the seismic behaviour of this structural typology, mainly in Latin-America, the lack of clear criteria for confined masonry design limits its application in Europe. In this work, a semi-empirical strength criterion for confined masonry, based on the diagonal shear failure of confined walls, is proposed. For this purpose, data mining is applied to a database of confined walls under cyclic loading tests, in order to clarify the variables that influence the shear strength. This study showed that the shear strength can be acceptably predicted by a multiple regression of the normal stress, diagonal shear strength, slenderness and masonry cross-section ratio of the walls. The relevance of longitudinal reinforcement of the confinement columns is low, with a significant contribution only in the post-cracking stage.